A TRIVIALLY PROPOSED FORMALISM OF MONSTROUS WAY OF UNIFICATION OF RELATIVITY AND QUANTUM PHYSICS USING 11– HYPERDIMENSIONAL HYPERCOMPLEX NUMBER SYSTEM UPTO DEKACADINION BASED ON THE ALGEBRAIC NORM OF THE GENERALIZED CAYLEY–DICKSON CONSTRUCTION - Deep Bhattacharjee; Sanjeevan Singha Roy; Pradipta Narayan Bose, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
From 1 to Monocadinion and extending till Dekacadinion a trivial wayout is presented for a unified approach of relativity and quantum mechanics in a trivial formulation using the Cayley – Dickson constructions in all the algebraic, modified and generalized forms subject to further research.